Fishing and bottom water temperature as drivers of change in maximum shell length in Atlantic surfclams (Spisula solidissima). (5th March 2016) - Munroe, D.M.; Narváez, D.A.; Hennen, D.; Jacobson, L.; Mann, R.; Hofmann, E.E.; Powell, E.N.; Klinck, J.M.
Abstract: Maximum shell length of Atlantic surfclams ( Spisula solidissima ) on the Middle Atlantic Bight (MAB) continental shelf, obtained from federal fishery survey data from 1982-present, has decreased by 15–20 mm. Two potential causes of this decreasing trend, fishery removal of large animals and stress due to warming bottom temperatures, were investigated using an individual-based model for post-settlement surfclams and a fifty-year hindcast of bottom water temperatures on the MAB. Simulations showed that fishing and/or warming bottom water temperature can cause decreases in maximum surfclam shell length (body size) equivalent to those observed in the fished stock. Independently, either localized fishing rates of 20% or sustained bottom temperatures that are 2 °C warmer than average conditions generate the observed decrease in maximum shell length. However, these independent conditions represent extremes and are not sustained in the MAB. The combined effects of fishing and warmer temperatures can generate simulated length decreases that are similar to observed decreases. Interannual variability in bottom water temperatures can also generate fluctuations in simulated shell length of up to 20 mm over a period of 10–15 years. If the change in maximum size is not genotypic, simulations also suggest that shell size composition of surfclam populations can recover if conditions change; however, that recovery could take a decade to become evident. Graphical abstract: Highlights: Maximum length of Atlantic surfclams ( Spisula solidissima ) has decreased by 20 mm. Possible drivers (fishing & temperature) were investigated with population models. Increasing bottom water temperature by 2 °C can cause the observed change. Sustained fishing at 20% can also cause the observed change. Interannually varying water temperatures can cause the observed change.